Perjodohan Dalam Pandangan Islam - M. Misbahul Amin (ADIDAS: Asosiasi Dosen Syari'ah STAI Darussalam Nganjuk, 2022)
Arranged marriage is not prohibited in Islamic law, unless the arrangement is forced and the individual being arranged is not consenting to it. A guardian (wali) is not allowed to impose their will and marry off someone under their guardianship without their permission. If a person has been forcibly married, they have the right to choose whether to continue or annul the marriage. Both the state and religion prohibit forced marriages. It's important to note that cultural practices and interpretations of religious laws may vary, and these statements reflect a general understanding of the principles related to arranged marriages in Islam. Specific rulings and practices may differ based on the interpretation of scholars and the legal framework of a particular region or community.